“Mirroring Yourself”: Peer Mentor Circle Support for International Graduate Student Transitions - Hyden, Brittany; Coryell, Joellen (Journal of International Students, 2022)
Transitioning to graduate school in the United States presents many challenges for international students including culture shock, academic shock, language barriers, and homesickness. As universities continue to bring international students to their classrooms, it is imperative that they feel welcome and supported. To this end, a university in the Southwest United States employed a peer mentor circle program aimed at easing the transition for international graduate students as they began their programs. Using Schlossberg’s (2011) transition theory, this study examined the moving in and moving through phases of eight new international graduate students as they participated in the peer mentor circle program with six current international graduate students. The study provides insight into the moving in phase of new international graduate students and found that the peer mentor circle program eases transition to graduate school and fosters movement toward the moving through phase of the transition model.